2006
DOI: 10.1007/s10295-006-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evaluation of the efficacy of microbial cell removal from fabrics

Abstract: The efficacy of microbial cell removal (EMR) from fabrics is a practically important indicator for the evaluation of cleansers and detergents. EMR is expressed quantitatively by the relative number of viable cells remaining on a fabric swatch after the treatment with these reagents. In order to count the viable cells on the swatch directly and rapidly, we have developed a unique microscopic imaging system with an ultra-deep focusing range. Standard swatches of cotton fabric were inoculated with microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Kinetics of solute transport traditionally have been measured with radiolabeled tracers. , Over the past two decades, transport has also been measured with fluorescently labeled tracers, including analogues of glucose, other monosaccharides, trehalose, amino acids, , peptides, toluene, and polyamines . Some fluorescent tracers are not labeled analogues but are naturally fluorescent compounds that fortuitously are transported by a transporter system of interest; for example, esculin is transported by type I plant sucrose transporters .…”
mentioning
confidence: 99%
“…Kinetics of solute transport traditionally have been measured with radiolabeled tracers. , Over the past two decades, transport has also been measured with fluorescently labeled tracers, including analogues of glucose, other monosaccharides, trehalose, amino acids, , peptides, toluene, and polyamines . Some fluorescent tracers are not labeled analogues but are naturally fluorescent compounds that fortuitously are transported by a transporter system of interest; for example, esculin is transported by type I plant sucrose transporters .…”
mentioning
confidence: 99%
“…The detailed components of the UDF Xuorescent system are described previously [4,5]. Ultra long distance industrial optical lenses (CFI Plan EPI SLWD 50 and 30, NIKON Co., working distance 17.0 and 24.0 mm, respectively) and a semi-automatic cell injection manipulator (InjectMan NI2, Eppendorf Co.) were integrated to assemble a cell manipulation system (Fig.…”
Section: Microscope and Manipulation Systemsmentioning
confidence: 99%
“…Currently, urgent needs exist in the detection of food pathogens in cooking environment [11,17] and microbial growth in damp garments after the laundry washing process [10,14]. To meet these needs, we have recently developed a ultra-deep focusing range (UDF) Xuorescent microscope system and applied it successfully to the evaluation of microbial cell removal from fabrics [4], and to the automatic mapping of viable microbial cells being distributed in the surface layer of cotton fabrics [5]. The next step is to isolate those single-cells for their identiWcation.…”
Section: Introductionmentioning
confidence: 99%
“…However it was difficult to modify available models at a reasonable cost to fit our specific resolutional purpose. Thus we developed a novel microscopic system with an UDF system (Fujioka et al, 2006). In combination with the staining of viable cells with a fluorescent glucose derivative, 2-NBDG (Yoshioka et al, 1996;Matsuoka et al, 2003), the UDF system was found to be useful for the rapid evaluation of the efficacy of microbial cell removal (EMR) from fabrics in the specific case of Candida albicans microbes greater than 5 A/ m. From a practical viewpoint, however, it is essential to establish a spatial resolution as high as 1-2 m. In this study, we have critically revised the principal image processing software.…”
mentioning
confidence: 99%